(untitled) (Research, Society and Development, 2025)
This study aimed to analyze the presence, growth, and bacterial resistance profile of microorganisms isolated from gym equipment surfaces in Teresina, Brazil. An experimental field study was conducted in three fitness centers, with samples collected from treadmills, leg extension machines, and straight bars. The samples were cultured on selective media and identified through Gram staining and biochemical tests (catalase and coagulase). Significant bacterial growth was observed in all samples, with a predominance of Gram-positive cocci, mainly staphylococci, indicating a microbiota typical of human contact. The antibiogram revealed that all isolates were sensitive to the tested antibiotics, showing no bacterial resistance. It is concluded that gyms can act as reservoirs for potentially pathogenic microorganisms, highlighting the importance of effective cleaning protocols and user awareness to prevent cross-contamination and ensure safer environments for physical activity.